PENGARUH KUALITAS PRODUK DAN PERIKLANAN YOUTUBE TERHADAP LOYALITAS PENGGUNA BRAND WARDAH KOSMETIK DI KOTA SEMARANG - Bunga Indah Permata; Apriatni Endang Prihatini (Jurnal Ilmu Administrasi Bisnis, 2018)
Beauty cosmetics are one of women’s most important things and basic needs to beautify their appearances and also as a skincare treatment. PT. Paragon Technology and Innovation is the one of manufacturers that creates a beauty cosmetic product. One of its product, Wardah Kosmetik with the tagline “inspiring beauty”, has a market share numbered as 34,5% in 2016 at national level. Meanwhile, at the number of counters from year 2013-2017, Wardah Kosmetik counter numbers in Semarang have decreased in comparison with Kudus which is significantly increasing and developing. That is caused by competition in beauty cosmetics market which is getting tighter both in product quality and advertisement that is used to preserve the hearts of consumers. This research’s aim is to know the influence given by product quality and Youtube advertising to Wardah Kosmetik consumers’ loyalty in Semarang. The result of the research shows that product quality and Youtube advertisements variables have a strong and positive influence to Wardah Kosmetik consumers loyalty in Semarang. Product quality and Youtube Advertisement variable shown as 0,856; it shows that both variables and consumers loyalty have a strong relation. Product quality variable on determination test (R square) shows that 71,9% of it influences consumers loyalty, meanwhile the rest of 28,1% is influenced by another factors. Youtube advertisement variable at determination test (R square) shows a number of 64,1% is influencing consumers loyalty while another 35,9% is influenced by another factors.